PENINGKATAN KOMPETENSI GURU PENDIDIKAN ANAK USIA DINI DI TK BINA HASANAH CIMINDI: COMPETENCE IMPROVEMENT OF EARLY CHILD EDUCATION TEACHERS AT BINA HASANAH CIMINDI KINDERGARTEN - JENAL ABIDIN; HAMIDAH; SITI HARUM NURESHARA (incrementapedia, 2023)
Teacher competence is one of  the benchmarks for the success of the education implemented. Therefore, qualified educators will be able to produce students who grow according to thei rstage of development. This ability is closely related to the ability of teachers to teach in the classroom. This includes the ability to manage classes and the ability of teachers to interact with students. The purpose of this study was to analyze several teacher competencies including teacher competence in pedagogic competence,  personality competence, socialcompetence, and teacher professional competence. The research method uses a qualitative descriptive analysi sapproach. The results of the study indicate that teachers have applied pedagogic competence, personality competence, social competence, and professional competence in classroom learning but still need to be improved. But the competence of its application In learning is still in the poor category. It is suggested that teachers canimprove their competence in classroom learning by participating in various competency development trainings.